Effects of Obesity on the Auditory Function of Children and Adolescents - Başer, Engin; Kendirci, Havva Nur Peltek (International Archives of Otorhinolaryngology, 2022)
Introduction Childhood and adolescent obesity is associated with insulin resistance, abnormal glucose metabolism, hypertension, dyslipidemia, inflammation, liver disease, and compromised vascular function.Objective We aimed to evaluate the effects of obesity on the auditory function and speech audiometry of children and adolescents.Methods Subjects with a body mass index (BMI) higher than +2 standard deviation (SD) were classified as obese, and subjects with normal BMI SD were classified as the control group. Blood samples were taken for glucose, insulin, and lipid profiles following an 8-hour fasting period, and a hepatobiliary ultrasound was performed. The homeostatic model assessment for insulin resistance (HOMA-IR) was calculated. The audiological evaluation included pure-tone audiometry (PTA), speech reception threshold (SRT), and speech discrimination score (SDS).Results The study included 100 children (50 girls) with obesity, with a mean age of 11.4 ± 2.9 years and 30 children with normal body weight, with a mean age of 11.9 ± 3.3 years. Of the children with obesity, 55% (n = 55) were found to have hyperlipidemia, 68% (n = 68) insulin resistance, and 21% (n = 21) hepatosteatosis. There were no statistically significant differences between children with obesity and the control group in terms of SDS or PTA, while SRT was found to be higher in children with obesity. There was no difference between obese children with or without hyperlipidemia, between obese children with or without insulin resistance, and between obese children with or without hepatosteatosis, according to hearing tests.Conclusion The result of the present study indicates that children with obesity are more prone to having auditory problems than the normal population. We recommend more frequent audiological evaluations, including speech audiometry, in children and adolescents with obesity problems
Keywords: childhood; adolescent; obesity; pure-tone audiometry; speech audiometry